Das armenische Kulturerbe in Berg-Karabach/Arzach und die Deutschen Dokumentation der Interkonfessionellen Tagung vom 9. Juni 2021 - Tamcke, Martin; Harutyunyan, Harutyun G.; Heller, Dagmar; Müller, Andreas; Schlarb, Egbert (Universitätsverlag Göttingen, 2021)
In its aftermath, the bad outcome of the 2020 Arzakh/Mountain Karabakh war for Armenia also prompted German theologians to launch an initiative to draw attention to the cultural heritage of the region. In doing so, they tied in with the histo rically grown connection between German science and Armenia, which is related to the interest in the richness and beauty of this culture, whose heritage has been repeatedly endangered by wars and foreign rule. In the shadow of the war of 2020, this documentary takes a first look at the rescued treasures from Arzakh/Mountain Karabakh and introduces initiatives and personalities who were and are committed to the country and its people. Translated with www.DeepL.com/Translator (free version)